Insights into the structure and function of the aggregate-reactivating molecular chaperone CLPB - Nagy, Maria (Kansas State University, 2009)
ClpB is a bacterial heat-shock protein that disaggregates and reactivates strongly aggregated proteins in cooperation with the DnaK chaperone system. ClpB contains two ATP-binding AAA+ modules, a linker coiled-coil domain, and a highly mobile N-terminal domain. It forms ring-shaped hexamers in a nucleotide-dependent manner. The unique aggregation reversing chaperone activity of ClpB involves ATP-dependent translocation of substrates through the central channel in the ClpB ring. The initial events of aggregate recognition and the events preceding the translocation step are poorly understood. In addition to the full-length ClpB95, a truncated isoform ClpB80, that is missing the whole N-terminal domain, is also produced in vivo. Various aspects of the structure and function of ClpB were addressed in this work. The thermodynamic stability of ClpB in its monomeric and oligomeric forms, as well as the nucleotide-induced conformational changes in ClpB were investigated by fluorescence spectroscopy. Equilibrium urea-induced unfolding showed that two structural domains-the small domain of the C-terminal AAA+ module and the coiled-coil domain-were destabilized in the oligomeric form of ClpB, which indicates that only those domains change their conformation or interactions during formation of the ClpB rings. Several locations of Trp-fluorescence probes were also found to respond to nucleotide binding. The biological role of the two naturally-occurring ClpB isoforms was also investigated. We discovered that ClpB achieves optimum chaperone activity by synergistic cooperation of the two isoforms that form hetero-oligomers. We found that ClpB95/ClpB80 hetero-oligomers form preferentially at low protein concentration with higher affinity than homo-oligomers of ClpB95. Moreover, hetero-oligomers bind to aggregated substrates with a similar efficiency as homo-oligomers of ClpB95, do not show enhanced ATPase activity over that of the homo-oligomers, but display a strongly stimulated chaperone activity during the reactivation of aggregated proteins. We propose that extraction of single polypeptides from aggregates and their delivery to the ClpB channel for translocation is the rate-limiting step in aggregate reactivation and that step is supported by the mobility of the N-terminal domain of ClpB. We conclude that the enhancement of the chaperone activity of the hetero-oligomers is linked to an enhancement of mobility of the N-terminal domains.
Keywords: Protein folding; Protein structure; Protein aggregation; AAA+ ATPase; Molecular chaperone; Biology, Molecular (0307); Chemistry, Biochemistry (0487)